Biochemical and biological characterization of Bothriechis schlegelii snake venoms from Colombia and Costa Rica - Prezotto Neto, José Pedro (2016)
Snakebites inflicted by the arboreal viperid snake Bothriechis schlegelii in humans are characterized by pain, edema, and ecchymosis at the site of the bite, rarely with blisters, local necrosis, or defibrination. Herein, a comparative study of Bothriechis schlegelii snake venoms from Colombia (BsCo) and Costa Rica (BsCR) was carried out in order to compare their main activities and to verify the efficacy of Bothrops antivenom produced in Brazil to neutralize them. Biochemical (SDS-PAGE and zymography) and biological parameters (edematogenic, lethal, hemorrhagic, nociceptive, and phospholipase A2 activities) induced by BsCo and BsCR snake venoms were evaluated. The presence of antibodies in Bothrops antivenom that recognize BsCo and BsCR snake venoms by enzyme-linked immunosorbent assay and Western blotting, as well as the ability of this antivenom to neutralize the toxic activities were also verified. SDS-PAGE showed differences between venoms. Distinctive caseinolytic and hyaluronidase patterns were detected by zymography. BsCo and BsCR showed similar phospholipase A2 activity. Strong cross-reactivity between BsCo and BsCR was detected using Bothrops antivenom with many components located between 150 and 35 kDa. BsCR was more edematogenic and almost fourfold more hemorrhagic than BsCo, and both venoms induced nociception. BsCR (LD50 5.60 mg/kg) was more lethal to mice than BsCo (LD50 9.24 mg/kg). Bothrops antivenom was effective in the neutralization of lethal and hemorrhagic activities of BsCo and BsCR and was partially effective in the neutralization of edematogenic and nociceptive activities. In conclusion, geographic distribution influences the composition and activities of Bothriechis schlegelii venoms. Bothrops antivenom cross-reacted with these venoms and was partially effective in neutralizing some toxic activities of BsCo and BsCR.